The Role of Diet Diversity and Diet Indices on Allergy Outcomes - D'Auria, Enza; Peroni, Diego G.; Sartorio, Marco Ugo Andrea; Verduci, Elvira; Zuccotti, Gian Vincenzo; Venter, Carina (Frontiers in Pediatrics, 2020)
Nutrients in foods are not eaten in isolation and food intake interacts in a complex manner, affecting health and disease outcomes. For this reason, focusing on the whole “pattern” of dietary intake instead of the single nutrients or groups of nutrients when studying diseases outcomes is increasingly appealing and growing. Diet diversity refers to the variety of foods being eaten, and the terms, diversity or variety, are often used interchangeably. When the overall diet is characterized by healthy foods, diet diversity will reflect a diversity/variety of healthy foods eaten over a period of time. The introduction of solid foods in the 1st year of life is considered a measure of increased diet diversity. Consuming a diverse range of foods and food allergens in the first year of life may increase intake of important nutrients and positively affect the gut microbiome structure and function. Intake of omega-3 fatty acids and fibers/prebiotics may be particularly important but more information is required about dose and which individuals are most likely to benefit. Increased diet diversity in the first year of life is also associated with reduced food allergy outcomes. In addition to diet diversity, diet indices are considered measures of overall diet quality and can be used as a simple assessment of dietary intake. The focus of this paper is to review and critically address the current knowledge of the association between diet diversity and diet indices and allergy outcomes. Based on the current evidence, we recommend the introduction of solid foods, including common allergenic solids, during the 1st year of life, according to the infant's neuro-developmental abilities and familial or cultural habits. For infants with severe AD and/or FA, medical assessment may be advisable before introducing common food allergens into the diet. Limited evidence exist about the role of diet indices in pregnancy and allergic disease in the offspring, and the most promising results indicate a reduction in childhood wheeze and/or asthma intake.